1981
DOI: 10.1136/bmj.282.6280.1917
|View full text |Cite
|
Sign up to set email alerts
|

Influence of cimetidine on pharmacokinetics of propranolol.

Abstract: Whole-blood propranolol concentrations were estimated for 12 hours after a single 80 mg oral dose was given in six patients taking cimetidine and two weeks after they had stopped the drug. Mean blood propranolol concentrations were higher throughout the sampling period when the patients were taking cimetidine than when they were not, and the difference was statistically significant between one and four hours (p <0 05). The mean relative bioavailability of propranolol, measured as the area under the concentrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
15
0
1

Year Published

1983
1983
1988
1988

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(16 citation statements)
references
References 14 publications
0
15
0
1
Order By: Relevance
“…The bioavailability of cimetidine (Puurunen & Pelkonen, 1979), inlignocaine and of paracetamol is reduced in creases the bioavailability of propranolol (Feely patients taking anticonvulsant drugs known to et Heagerty et al, 1981) and chlorproduce enzyme induction (Perucca & Richens methiazole . Labetalol, a 1979a, b;Perucca et al, 1980).…”
Section: Introductionmentioning
confidence: 99%
“…The bioavailability of cimetidine (Puurunen & Pelkonen, 1979), inlignocaine and of paracetamol is reduced in creases the bioavailability of propranolol (Feely patients taking anticonvulsant drugs known to et Heagerty et al, 1981) and chlorproduce enzyme induction (Perucca & Richens methiazole . Labetalol, a 1979a, b;Perucca et al, 1980).…”
Section: Introductionmentioning
confidence: 99%
“…Castleden et al (1975) found that given the same oral dose, substantially greater plasma levels were attained in elderly subjects compared with younger ones. Heagerty et al (1981) showed that concurrent cimetidine therapy led to both a higher blood propranolol concentration and relative bioavailability. Patel et al (1983) demonstrated that the area under the curve for propranolol administered per vaginam was significantly greater than that after oral administration.…”
Section: Discussionmentioning
confidence: 99%
“…Cimetidine is a potent inhibitor of the metabolism of a wide variety of drugs, including theophylline [10][11][12], acetaminophen [13][14][15], hexobarbital [16,17], aminopyrine [16][17][18], caffeine [18,19], phenacetin [18], phenytoin and antipyrine [20], warfarin [21], coumarin derivatives [22,23], benzo[a]pyrene [17,22], benzodiazepines [24], and propranolol [25]. The mechanism of inhibition of cimetidine, which has an imidazole ring struc ture, is unclear [reviewed in 1], The wide spectrum of drug metabolism that can be inhibited by cimetidine, however, is reminiscent of ellipticine, an antineoplastic agent which also elicits a strong type II difference spectrum and contains an imidazole ring [26].…”
Section: Discussionmentioning
confidence: 99%